(untitled) (Quinto Sol, 2019)
This study addresses long-term changes in the morphology of the Fabril Financiera group. It extends over the years of Import Substituting Industrialization (ISI) between the crisis of 1929 and the mid-1970s. This period includes the onset, boom and loss of economic importance of the financial industrial group. Indeed, in the context of the crisis, Compañía General Fabril Financiera was founded in 1929. Although the economic group survived until the beginning of the 1990s, in this work we study its formation, expansion and the beginnings of its decline in an extended period from the year of its founding until the mid-1970s. The article intends to contribute with new empirical evidence, both quantitative and qualitative, to the broader discussion on the participation of the economic groups in the economic development of Argentina in the twentieth century.